2013
DOI: 10.4236/jep.2013.43031
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Sorption of Lead and Nickel from Solutions by Flame of the Forest (<i>Delonix regia</i>) Pods: Kinetics and Isothermic Study

Abstract: Batch adsorption techniques were used to study the biosorption of Lead and Nickel from aqueous solutions by Flame of the forest pods. The effects of optimum pH, contact time, metal ion concentration, biosorbent dose, biosorbent particle size and the presence of sodium, calcium and magnesium interfering ions on the sorption were investigated. Experimental results showed that Delonix regia biomass was effective in removing these metals from aqueous solutions as the equilibrium biosorption of both metals was atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Seeds or pods, or fruits used as an adsorbent Festus et al (2013) investigated on the flame of the forest (Delonix regia) tree pods for the sorption of lead and nickel ions from solution. The result showed that Delonix regia effectively removed these elements from aqueous solution, and equilibrium sorption of both metals was attained within 60 min-utes of interaction and 98% removed metals.…”
Section: Bark As An Adsorbentmentioning
confidence: 99%
“…Seeds or pods, or fruits used as an adsorbent Festus et al (2013) investigated on the flame of the forest (Delonix regia) tree pods for the sorption of lead and nickel ions from solution. The result showed that Delonix regia effectively removed these elements from aqueous solution, and equilibrium sorption of both metals was attained within 60 min-utes of interaction and 98% removed metals.…”
Section: Bark As An Adsorbentmentioning
confidence: 99%
“…in the mesoporousactivated carbon for the degradation of sulphonated phenolic compounds in wastewater. Delonix regia derived AC has also been utilized to remove Hg [34], Pb and Ni [35].…”
Section: Application Of Phytomass-derived Ac As An Adsorbentmentioning
confidence: 99%
“…Wilson's and Alzheimer's diseases, mental illness, Indian childhood cirrhosis and schizophrenia are also reported to be caused by excess copper in the blood (Brewer, 2007;Faller, 2009;Hurean and Faller, 2009). Nickel has detrimental effects on human health, resulting in allergic dermatitis, immunologic urticaria, and immediate and delayed hypersensitivity (Festus et al, 2013). All nickel compounds, except for metallic nickel, have been classified as human carcinogens by the International Agency for Research on Cancer (IARC, 1990) and the U.S. Department of Health and Human Services (DHHS, 1994).…”
Section: Introductionmentioning
confidence: 99%